Hubungan Tingkat Pengetahuan dan Dukungan Keluarga Dengan Kepatuhan Diet Pasien Hipertensi di Rumah Sakit Jakarta - Cahyani Hia, Widia; Maria Astrid (Journal of Pubnursing Sciences, 2023)
Background: Hypertension is the main and most common cause of acute coronary syndromes such as "heart attacks". Adhering to a hypertension diet is an important thing to do to keep blood pressure stable. Purpose: the purpose of the study was to determine the relationship between the level of knowledge about hypertension and family support with dietary compliance of hypertensive patients at Jakarta Hospital. Method: This research method is quantitative research with a descriptive correlational design and uses a cross-sectional study approach. The sample of 169 patients, using a purposive sampling technique. Collecting data using a questionnaire. Result: From the results of the univariate analysis, the characteristics of the majority of respondents aged > 60 years old (64%), male (54%), good knowledge (47%), poor family support (41%), and dietary compliance (63%). Bivariate analysis using Kendal's tau C test showed a significant relationship between knowledge about hypertension and family support with dietary adherence in hypertensive patients, with each p-value = 0.000. Conclusion: Patients with good knowledge and family support, the patient's adherence to a hypertension diet.